2014
DOI: 10.1534/genetics.114.168799
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Saccharomyces paradoxus Chronological Lifespan by Retrotransposons in Certain Media Conditions Is Associated with Changes in Reactive Oxygen Species

Abstract: Retrotransposons are mobile DNA elements present throughout eukaryotic genomes that can cause mutations and genome rearrangements when they replicate through reverse transcription. Increased expression and/or mobility of retrotransposons has been correlated with aging in yeast, Caenorhabditis elegans, Drosophila melanogaster, and mammals. The many copies of retrotransposons in humans and various model organisms complicate further pursuit of this relationship. The Saccharomyces cerevisiae Ty1 retrotransposon wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 65 publications
(112 reference statements)
1
17
1
Order By: Relevance
“…In contrast, the many retrotransposition-competent Ty1 elements inhabiting Saccharomyces genomes encode their own inhibitor and, therefore, must balance mutations altering p22 potency with those affecting GAG fitness. Since Ty1 GAG or p22 coding regions have not been detected as an exapted gene capable of inhibiting Ty1 movement, the graduated retrotransposition rate provided by CNC may benefit Saccharomyces and Ty1, as suggested by recent work relating increases in Ty1 copy number with longer chronological life span (95). The Ty1-p22 interaction appears to directly block assembly of functional VLPs in a dosedependent manner and to our knowledge represents a novel and effective way to allow some but not rampant retroelement movement.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, the many retrotransposition-competent Ty1 elements inhabiting Saccharomyces genomes encode their own inhibitor and, therefore, must balance mutations altering p22 potency with those affecting GAG fitness. Since Ty1 GAG or p22 coding regions have not been detected as an exapted gene capable of inhibiting Ty1 movement, the graduated retrotransposition rate provided by CNC may benefit Saccharomyces and Ty1, as suggested by recent work relating increases in Ty1 copy number with longer chronological life span (95). The Ty1-p22 interaction appears to directly block assembly of functional VLPs in a dosedependent manner and to our knowledge represents a novel and effective way to allow some but not rampant retroelement movement.…”
Section: Discussionmentioning
confidence: 80%
“…Another recent study analyzed Ty1 retrotransposon expression and mobility during chronological aging in S. paradoxus (VanHoute & Maxwell, 2014). Increased expression and mobility of retrotransposons with age have been found in nearly every aging model and thought to promote genome instability during aging (Moskalev et al ., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…However, this study showed that, while the strain expressing Ty1 element had 40-fold increased mobility to the rDNA region, neither Ty1 mobility nor increased mutation rate of a representative Ty1 gene led to chronological lifespan decrease. Furthermore, increased expression of a Ty1 could extend chronological lifespan under certain conditions (VanHoute & Maxwell, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…HIV-1 CA’s sensitivity to mutation or genetic fragility is comparable to what we see with Ty1 Gag, as our CNC R analysis supports the idea that Ty1 Gag is under strict structural constraint (Tucker, et al 2015). Lastly, since Ty1 GAG or p22 sequences have not yet been detected as a domesticated gene, the graduated rate provided by CNC may benefit Saccharomyces and Ty1, such as extending chronological life span (VanHoute and Maxwell 2014). …”
Section: A New Paradigm For Inhibiting Gag Functionmentioning
confidence: 99%